Jejak pengusaha wanita: Tinjauan bibliometrik di seluruh dunia - Noor Wahid, Nisa; Firmansyah, Irman; Andriani , R. Neneng Rina (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This research analyzes trends in scientific publications regarding women entrepreneurs in different countries using a bibliometric approach. By collecting and analyzing publication data from various sources, this research identifies changes and developments in research on women entrepreneurs over time. Key findings include an increase in the number of scientific publications related to women entrepreneurs over time, with a shift in focus from social and cultural aspects towards multidisciplinary analyses involving economic, business, gender, and innovation aspects. The results of the analysis also reveal that women entrepreneurs have a significant impact in various economic sectors, bringing innovation and leadership that contribute to the growth of businesses and society as a whole. These findings have important implications for business practitioners, policymakers, and academics in understanding the challenges and opportunities faced by women entrepreneurs. This research contributes to our understanding of the important role of women entrepreneurs in the global economy and encourages further research to deepen our understanding of the impact of technology and other aspects affecting women entrepreneurs in a sustainable context.